(untitled) (Communication & Society, 2023)
Against the backdrop of the new attention economy (Giraldo-Luque & Fernández Rovira, 2020), which is based on attracting audience interest, this research analyses the production and distribution of media content through the emerging Telegram platform. Attracting the attention of the audience has become the main objective of the media in the digital environment. To achieve this aim, more personalised content is now being produced, and attempts are being made to reach the user in a more direct and personal way through instant messaging platforms, especially Telegram. Through a methodology based on data triangulation, documentary analysis, interviews, registration techniques, analysis sheets, as well as direct and indirect observation (Fernández-Ballesteros, 2004), this study addresses the rise of Telegram in journalism, in addition to the way in which the Spanish media distribute, produce, and use the information, as well as interaction with the audience. To this end, a strategic sample has been used, the results of which are applicable to the media analysed. The results of this research show that nearly half of the media analysed produce content and inform the user without considering interaction, while others try to approach the user with language that is informal and friendly, or through multimedia content such as videos, emoticons, and others. The media have suddenly appeared on Telegram in search of new market niches where they can produce content for new users, thereby pursuing the rationale of the attention economy.